PENGEMBANGAN MEDIA MOBILE LEARING MATA PELAJARAN BAHASA ARAB METODE DIRECT DI MADRASAH TSANAWIYAH - Muhamad Irwan Wahyudi; Khaerudin Khaerudin (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
The background in this research based on low utilization of media in Arabic subjects at MTsN 24 Cakung, East Jakarta. This study aims to produce mobile learning media of Arabic with direct methods in Madrasah Tsanawiyah. This type of research is the development research by Hannafin and Peck model using 3 stages: (1) the needs analysis phase, (2) the design phase and (3) the development and implementation phase. The results showed that: (1) The results of the expert review of the subject experts at